Risk Factors That Lead To Poor Glycemic Control In Type 2 Diabetic Patients Attending Al Diwaniya Diabetes Mellitus Center In 2023 - Lara Noori Hamza; Hassan Raji Jallab (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Diabetes mellitus (DM) is the most common metabolic disorder worldwide. DM is the most common chronic illness in adults. It is estimated that 300 million people will have DM by 2025, and it will reach approximately 439 million and the prevalence is estimated to be 7.7% by 2030. The decrease of blood glucose levels in patients with DM decreases the mortality and morbidity rates significantly.Objective: To identify the potential risk factors of poor glycemic control among patients having type2 Diabetes mellitus in Al-diwaniya city. Methods: A total of 340 patients were included in the study. This was cross sectional study conducted in the Diabetes Center at Al-diwaniya city, Iraq, from period of 1st of February to the 1st September2023. Based on the cutoff point of Glycosylated hemoglobin of 7, the poor control were the patients with (Glycosylated hemoglobin is ≥ 7) and the good control were the diabetic patient with Glycosylated hemoglobin is <7. A questionnaire developed to gather the demographic, lipid profile, disease characteristics and lifestyles behaviors and filled by the researcher through direct interview. Results: The total number of poor controls was 221 and the good control was 119 patients. There was no significant difference between the two groups regarding sex, age, marital status and occupation. A significant association was observed between the control status and high education level (p=0.001) dyslipidemia (p=0.001), cholesterol level (P=0.002), high TG level (p<0.001), and LDL level (p=0.025). Smoking, Body Mass Index and HDL level were not significant factors (p>0.005). All disease characteristics including the duration, family history of DM, FBS, type of medication were significant factors (p<0.001). Lifestyles behaviors including self-monitoring, healthy diet, physical activity, and adherence were significant factors (p<0.001). Conclusion: The most important potential risk factors for poor control diabetes were dyslipidemia, poor adherence and longer duration of diabetes. Enhancement of education of the patients and their healthcare providers on these factors are great benefit in glycemic control.